Avoiding falls - Rein Tideiksaar (Thomson Delmar Learning, 2006)
Falls, whether causing injury or not, are key issues facing long-term care facilities today. Avoiding Falls: A Guidebook for Certified Nursing Assistants realizes the important role nursing assistants have in the care of their clients and that they play a key part in preventing falls. This easy-to-read product aims to raise the awareness of nursing assistants about the different causes of falling; the harmful consequences of falls on the clients' physical and mental well-being and steps to prevent falls from occurring